Model za poučevanje poslovne angleščine s študijo primera - Dostal, Mateja (Šolsko polje, 2008)
The use and experience of the case study method is one of the more demanding tests for a teacher. While the communication spontaneously emerging during thepresentation, analysis and discussion phases of a case study may to some extent be planned and manageable, each case study represents a new challenge every time. It is of key importance that a teacher be equipped with the necessary fund of experience, skills and knowledge to be able to function as acapable facilitator i.e. moderator among groups and individuals. The model for efficient teaching and learning Business English is based on the assumption, that the use of the case study method permits a complete learning context for foreign language learning and makes the use of the authentic language context in heterogeneous classes possible. It provides the richness of the language input and high motivational context where language is created.The users are facilitated to create their own texts and contexts resulting from an activity and are motivated for social interaction and learning from others. The success at a cognitive and language level is smoothed by motivating the users to take risk in various language uses and find ways to express what they need to express.
Keywords: metodika; poslovna angleščina; študija primera; tuji jeziki; učne metode